Adaptability of participatory backcasting to e-backcasting for inclusive sustainable city visioning for African cities: a prototyped study Of Abuja, Nigeria - Achuenu, Ache Stella (My University, 2019)
The implementation process of the envisioned future for Abuja as the capital city of Nigeria since 1975 was ill-fated from the start, mainly due to the pattern of exclusion in the governance style, as well as the rigid execution guided by a modernist-inspired master-plan. The resultant sustainability challenges facing the city today include escalating segregation among its rich and poor residents, a hostile relationship between residents and city-administration and a stubborn indifference to the city’s ecological footprint. Provoked by these challenges, this study applied action-research to guide the prototyping of e-backcasting for sustainable city transitioning for Abuja over the next 50-years, with the key focus on participation and inclusivity. The potential of e-backcasting as a participation enhancement-tool was explored by bridging e-governance and conventional backcasting (face-to-face) while leveraging the rapidly maturing Web 2.0 socio-media tools. The process involved four iterative steps which entailed the application of four social-media tools (e-mails, Facebook, blogs and WhatsApp). Of the 644 possible participants initially contacted, 302 participants consented (26 on email, 58 on Facebook, 9 on blogs and 209 on WhatsApp) and remained engaged across all four iterations. Of these, 34 participants were deemed to be experts while 268 participants were deemed to be common citizens. 147 of the 302 participants reported that they were generally satisfied with their participation experience and felt that the approach would be useful for inclusive city-planning in Nigeria especially in facilitating responsive pathways for sustainable city transitioning. In contrast, 59 participants reported dissatisfaction in their experience with the process while 96 participants reported an undetermined/neutral experience. The key inadequacies with the recruitment, participation and inclusivity mainly related to time and technology access, language and low-familiarity with the process and subject-matter of the study. The study recommends further prototyping within Abuja’s e-Governance platform in order to allow for additional evaluation and establishment of institutional capacity for full implementation. In addition, the study concludes that the initial process of reaching out for awareness-raising and recruitment of participants constitutes the most critical stage towards ensuring participation and inclusivity.
A thesis submitted to the Faculty of Engineering and the Built Environment, University of Witwatersrand, Johannesburg, in fulfilment of the requirements for the Degree of Doctor of Philosophy, Johannesburg, July 2019
Keywords: Sustainable development; Social integration